Green synthesis of ZnO nanoparticles from citrus hystrix extracts for antibacterial application - Al-Wafiy Lauthfi, M. A.; Yusoff, M. Z. M.; Kamil, S. A.; Mohamad, S. A. S.; Abdullah, C. A. C.; Saidin, N. U. (Virtual Company of Physics, 2024)
This study investigates the eco-friendly synthesis of zinc oxide nanoparticles (ZnONPs) using Citrus hystrix extract as a reducing agent. HRTEM and SAED analyses confirmed spherical nanoparticles (~20 nm) with a hexagonal wurtzite structure. Photoluminescence (PL) results showed that lower zinc acetate concentrations (0.1 M) produced higher luminescence intensity, indicating an inverse relationship between concentration and optical properties. Antibacterial tests against five bacterial strains revealed greater efficacy at lower concentrations (0.1 M and 0.2 M), likely due to reduced aggregation. Raman spectroscopy confirmed the hexagonal wurtzite phase. Optimizing nanoparticle concentration could enhance applications in optoelectronics and catalysis. Lower concentrations (0.1 M and 0.2 M) often exhibited stronger antibacterial action against bacterial strains such S. aureus, E. coli, S. typhimurium, K. pneumoniae, and B. subtilis. The antibacterial performance of the ZnONPs was concentration-dependent. Lower doses produced the largest zones of inhibition; 0.2 M was the most effective against S. aureus, while 0.1 M was the most effective against S. typhimurium and B. subtilis.